MODEL PERLINDUNGAN HUKUM TERHADAP KEBIJAKAN PELAYANAN KESEHATAN MASYARAKAT MISKIN DI KABUPATEN BANYUMAS - Sri Hartini; Tedi Sudrajat; RahadiWasi Bintoro (Faculty of Law, Universitas Jenderal Soedirman, 2012)
The legal protection to health care, especially for the poor directed to apply the principles of holistic, unity, evenly, acceptable and achievable. Therefore, this article is useful to explain the rules, policies and barriers that occur in its implementation. Based on the classification, there are 3 part in implementing legal protection and health services include arrangement of the essence of health development, funding and health service delivery. Policies that have been implemented in Banyumas includes a health card namelly jamkesmas, jamkesda, and jampersal. In fact, there are resistance from the aspect of substance, structure and legal culture that affects all three models of its implementation. Key words: legal protection, health care, the poor